Análise de compatibilidade entre o Plano Plurianual 2020-2023 e o Plano Estratégico de Governo 2019-2022 do estado de Sergipe - Barbosa, Arthur Lincoln Diógenes Guedes (2021)
This work aims to investigate the compatibility between two government planning instruments that define the priorities and goals of the State Government of Sergipe, particularly the Government Strategic Plan for 2019-2022 and the Pluriannual Plan for 2020-2023, using as scope of research the thematic areas of education and sport. In Brazil, the Federal Constitution established that planning is determinative for the public sector, helping the State to fulfill its role in favor of citizens, through public policies that materialize social rights and give results. In Sergipe, we raised the question about the mentioned planning instruments, due to the fact that they were prepared by different state secretariats. Considering this, the present work sought to carry out an analysis of compatibility between these two instruments, using the thematic areas of education and sport as research scope. For this, a research was carried out in three stages, with a survey on the elaboration process of the plans, the characterization of the internal structure of the plans, and, lastly, an analysis of compatibility according to the defined criteria. In the end, it was observed that the plans, despite having the same strategic identity, are indistinctly incompatible, at least for the areas of education and sport, showing that the government’s planning process of the State of Sergipe resulted in the appointment of different priorities between the Government Strategic Plan for 2019-2022 and the Pluriannual Plan for 2020-2023.